2020
DOI: 10.1101/2020.12.10.420695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Similarities and differences between IL11 and IL11RA1 knockout mice for lung fibro-inflammation, fertility and craniosynostosis

Abstract: Genetic loss of function (LOF) in IL11RA infers IL11 signaling as important for fertility, fibrosis, inflammation and craniosynostosis. The impact of genetic LOF in IL11 has not been characterized. We generated IL11-knockout (Il11-/-) mice, which are born in normal Mendelian ratios, have normal hematological profiles and are protected from bleomycin-induced lung fibro-inflammation. Noticeably, baseline IL6 levels in the lungs of Il11-/- mice are lower than those of wild-type mice and are not induced by bleomyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Severe respiratory diseases such as IPF and SARS-COV-2 pneumonia are associated with defects in alveolar epithelial repair and irreversible loss of alveolar epithelial cells, which ultimately leads to fibrosis and a decline in lung function. We previously discovered an important role for IL11 in lung fibrosis, mediated via its profibrotic activity in lung fibroblasts and IL11 expression was confirmed in diseased fibroblasts in the current study ( 22, 25, 38 ). Here, we show that IL11 is specifically upregulated in aberrant alveolar epithelial cells in human PF and its expression is associated with pathological pro-EMT and inflammatory gene signatures in diseased epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…Severe respiratory diseases such as IPF and SARS-COV-2 pneumonia are associated with defects in alveolar epithelial repair and irreversible loss of alveolar epithelial cells, which ultimately leads to fibrosis and a decline in lung function. We previously discovered an important role for IL11 in lung fibrosis, mediated via its profibrotic activity in lung fibroblasts and IL11 expression was confirmed in diseased fibroblasts in the current study ( 22, 25, 38 ). Here, we show that IL11 is specifically upregulated in aberrant alveolar epithelial cells in human PF and its expression is associated with pathological pro-EMT and inflammatory gene signatures in diseased epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…Although mice globally and germline deleted for Il11ra1 (30) are not protected from AILI (19), which we confirmed, we believe that this may, in part, be explained by off-target effects at the Il11ra1 locus, which we documented. Furthermore, there are unique features seen in the Il11ra1 KO mouse that are not apparent in Il11 null mice (31). Our studies advise caution against using a single genetic model on one genetic background for the study of AILI, and we suggest that loss-and gain-of-function approaches across genetic models are preferred, especially if complemented by specific pharmacologic interventions.…”
Section: Discussionmentioning
confidence: 83%
“…We recently found that, although Il11ra1 KO mice have similarities with a globally deleted Il11 mouse (Il11 KO), they also have differences in some phenotypes (31) and also in expression of Ccl27a (fig. S9, D and E).…”
Section: Mice Deleted For Il11 Are Protected From Ailimentioning
confidence: 99%
“…39 Genetic LOF in IL11RA in mice and humans is associated with incompletely penetrant craniosynostosis and delayed tooth eruption but such mice and humans appear otherwise healthy with normal lifespans. 39–41 Furthermore, long-term administration of either anti-IL11 or anti-IL11RA to mice has not been associated with side effects. 27 With the right pharmacokinetic profile, antibody-based therapies can be administered subcutaneously monthly, even six-monthly, which may be acceptable regimen for the long-term administration of antibodies that inhibit IL11 signaling to patients with MFS.…”
Section: Discussionmentioning
confidence: 99%